Examining Irish nationalism in the context of literature, culture and religion a study of the epistemological structure of nationalism - O'Brien, Eugene, 1958- (Lewiston, N.Y. : Edwin Mellen Press, 2002)
This study argues that it is only through its epistemological perspective that nationalism can be properly analyzed. It goes on to offer such an analysis, utilizing the work of Jacques Lacan. This study contents that the captation of the self by a reflected, two-dimensional image of that self is the sine qua non of the epistemology of nationalism, as a sense of group selfhood is defined performatively through this process. The strong connections between nationalism and religion are examined Finally, the supposed difference between political nationalism and 'cultural nationalism' is interrogate.
Includes bibliographical references.
Description based on print version record.
Keywords: English literature -- Irish authors -- History and criticism; Nationalism and literature -- Ireland -- History; Nationalism -- Religious aspects; Nationalism -- Ireland -- History; Nationalism in literature; Ireland -- In literature; Ireland -- Civilization; Ireland -- Religion; English literature -- Irish authors -- History and criticism; Ireland -- Civilization; Ireland -- In literature; Ireland -- Religion; Nationalism -- Ireland -- History; Nationalism -- Religious aspects; Nationalism and literature -- Ireland -- History; Nationalism in literature; Literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Electronic books